2021
DOI: 10.3389/fmars.2021.707999
|View full text |Cite
|
Sign up to set email alerts
|

Fishing Effort and Associated Catch per Unit Effort for Small-Scale Fisheries in the Mozambique Channel Region: 1950–2016

Abstract: The Mozambique Channel region in East Africa has diverse marine ecosystems and serves as a migratory corridor for economically important species. Local and foreign industrial fisheries operate in the Mozambique Channel, but regional small-scale fisheries are the crucially important fisheries that provide food security, livelihoods, and economic opportunities for rural coastal communities. This study reconstructed and investigated trends in the fishing effort and catch per unit effort (CPUE) of small-scale mari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 42 publications
3
15
0
Order By: Relevance
“…This clearly indicates that increasing fishing capacity in the absence of effective and restrictive management actions may intensify the risk of overexploitation. These findings concur with Zeller et al (2021) who reported that CPUE declined by 91% across the Mozambique Channel region as a result of motorization and growth in vessel numbers during the period 1950-2016. Also, Silas et al (2020;2021) observed that artisanal fishing vessels, which are dominant in the nearshores of coastal areas in Tanzania, have resulted in overexploitation of fisheries resources as signified by decreasing CPUE.…”
Section: Contribution Of Fisheries To Livelihoods Improvementsupporting
confidence: 91%
“…This clearly indicates that increasing fishing capacity in the absence of effective and restrictive management actions may intensify the risk of overexploitation. These findings concur with Zeller et al (2021) who reported that CPUE declined by 91% across the Mozambique Channel region as a result of motorization and growth in vessel numbers during the period 1950-2016. Also, Silas et al (2020;2021) observed that artisanal fishing vessels, which are dominant in the nearshores of coastal areas in Tanzania, have resulted in overexploitation of fisheries resources as signified by decreasing CPUE.…”
Section: Contribution Of Fisheries To Livelihoods Improvementsupporting
confidence: 91%
“…Many countries were sampled insufficiently to determine the national-level status of fishing. Yet, there appears to be a propensity to reduce fish populations in nearshore coral reefs in this region to about one half the stock values where MMSY is achieved , Zeller et al 2021. The patterns observed here and from models indicate that over-fishing is pervasive even in the region's many low compliance marine reserves (McClanahan et al 2015.…”
Section: Discussionmentioning
confidence: 67%
“…Catch per unit effort is a basic fisheries science often used as a first-order evaluation of board trends in likely relative abundance or relative biomass trends over time of the underlying fish stocks [11][12][13]. While CPUE has its limitations, it can be useful in long term trend monitoring of a fishery, particularly where more detailed data and stock assessments do not exist (Stamatopoulos, 2022) and open or semi open access fisheries predominate, i.e., where restrictive fisheries management actions may be absent or ineffective [13]. Based on the catch per unit effort analysis results for Silver pomfret, it was found the highest CPUE value was the payang gear.…”
Section: Catch Per Unit Effortmentioning
confidence: 99%